Among human macrophages polarised to different phenotypes, the M-CSF-oriented cells present the highest pro-inflammatory response to the rheumatoid arthritis-specific immune complexes containing ACPA. Issue 12 (23rd March 2016) - Clavel, Cyril; Ceccato, Laurie; Anquetil, Florence; Serre, Guy; Sebbag, Mireille
Abstract : Objectives: In the inflamed synovium of patients with rheumatoid arthritis (RA), autoantibodies to citrullinated proteins (ACPA) probably form immune complexes (IC) on deposits of citrullinated fibrin. We showed that in vitro such ACPA-IC activate a pro-inflammatory cytokine response in M-CSF-differentiated macrophages. Our objective was to evaluate how macrophage polarisation influences this response. Methods: CD14-positive monocytes from healthy donors were cultured in the presence of M-CSF, IFN-γ, interleukin (IL)-4 or IL-10. Expression of markers specific for polarised macrophages was analysed by flow cytometry. Their cytokine secretion was prompted by in vitro generated autoantibodies to citrullinated proteins immune complexes (ACPA-IC) and assayed in the culture supernatants. Results: IFN-γ-polarised cells exhibited high levels of CD64 and CD80. Low expression of CD14 and high expression of CD206 characterised the IL-4-polarised cells. Exposure to IL-10 or M-CSF raised the expression of CD14, CD32 and CD163. The two cell types lacked CD80 and exhibited similar expression of CD64, CD200R and CD206. In response to ACPA-IC, the secretion of IL-1β, IL-6 and IL-8 was similar among cells exposed to IFN-γ, IL-4 or IL-10. However, the later cells were associated with the highest IL-1Ra:IL-1β ratio and the lowest tumour necrosis factor (TNF)-α:IL-10 ratio. Conversely, M-CSF-exposed cells secreted the highest levels of pro-inflammatory cytokines, exhibited a high TNF-α:IL-10 ratio and the lowest IL-1Ra:IL-1β ratio. Conclusions: Despite their phenotypic similarity, IL-10-polarised and M-CSF-polarised macrophages clearly differ in their cytokine response to ACPA-IC. M-CSF-polarised cells exhibit the highest pro-inflammatory potential. Since M-CSF is abundant in the RA synovium, therein it probably drives macrophages towards a strong pro-inflammatory cytokine response to the locally formed ACPA-IC.